PENATAAN PERMUKIMAN NELAYAN BERBASIS EKOKULTUR DI KELURAHAN BAROMBONG KOTA MAKASSAR [ECOCULTURE DEVELOPMENT OF A FISHERMEN SETTLEMENT IN BAROMBONG VILLAGE, MAKASSAR] - Andi Asmuliany; Andi Annisa Amalia; Mutmainnah Mutmainnah (Jurnal Sinergitas PKM & CSR, 2020)
The locus of community service activities is a residential corridor node by exploring the communal space of fishermen in the Biringkassi Barombong Village. The concept of ecoculture is a concept that combines ecological aspects, namely the fishermen's environmental ecosystem and the culture of the community, namely Bugis Makassar in managing fishermen settlements towards livable and sustainable livelihood. The method used in this community service is the Regional Arrangement Method with a participatory ecocultural approach. making mockups of existing areas, FGD identification of communal spaces, drafting of concepts, agreement on the arrangement of communal spots, and activities of structuring communal spots. The structuring of the Biringkassi Barombong Fishermen Village is a result of the community's contribution in increasing the environmental assets of the settlements owned by the fishing community through he adoption of the Bugis Makassar ornament and the setting of the shared area and the use of natural colors as a symbol of closeness to the sea.Bahasa Indonesia Abstrak: Lokus kegiatan pengabdian adalah node koridor permukiman dengan mengeksplorasi ruang komunal nelayan Kampung Biringkassi Barombong. Konsep ekokultur merupakan konsep yang mengkombinasikan aspek ekologi yaitu ekosistem lingkungan nelayan dan budaya masyarakat yaitu Bugis Makassar dalam menata permukiman nelayan menuju layak huni dan sustainable livelihood. Metode yang digunakan pada kegiatan pengabdian ini adalah Metode Penataan Kawasan dengan pendekatan partisipatif yang ekokultur. pembuatan maket eksisting kawasan, FGD identifikasi ruang komunal, penyusunan konsep, penyepakatan spot komunal penataan, dan kegiatan aksi penataan spot komunal. Penataan Kampung Nelayan Biringkassi Barombong merupakan hasil kontribusi masyarakat dalam peningkatan aset-aset lingkungan permukiman yang dimiliki oleh komunitas nelayan melalui adopsi ornamen Bugis Makassar dan setting area yang digunakan secara bersama dan penggunaan warna alami sebagai simbol kedekatan dengan laut.